EFFECT OF DIRECT INTEGRATION OF LABORATORY TESTING AND REAL-TIME PATIENT DATA MANAGEMENT ON PRECISION DOSING OF HIGH-RISK PATIENTS IN AN ASTHMA CLINIC - Ghazi N. Almutairi; Feras S. Alromaih; Hesam A. Aljelaud; Mohammed H. Kariri; Faisal K. Almutairi; Rakan M. Alassaf; Abdulmohsen M. Faqiri; Turki H. Alharbi; Feras S. Almalik; Abdullah E. Alfalah; Naif F. Almutairi (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Precision dosing is critical for high-risk patients in tertiary hospitals as any delays in intervention may result in negative outcomes. The goal of this research is to assess how the incorporation of real-time laboratory data into clinical workflows affects drug related side effects as well as patient care in terms of the achievement of suitable therapeutic targets.Methods: For the purpose of this retrospective observational study, we have included 500 patients requiring accurate dosing of their medications, at a tertiary hospital. Data pertaining to clinical outcomes, time relating to dose adjustment, occurrence of adverse drug reactions and achievement of therapeutic target were collected before and after the introduction of the real time laboratory data integration approach.Results: Incorporation of real-time lab data helped vancomycin patients achieve therapeutic targeting of 85% from an outset of 55% while warfarin user’s achievement improved from 60% to 88%. Adverse drug reactions, including nephrotoxicity and bleeding, decreased from 25% to 10% and 20% to 8%, respectively. The time to dose adjustment also fell from 4.8 ± 2.1 hours to 1.2 ± 0.8 hours. Other metrics related to patient outcome also improved with a decrease in length of hospital stay by 2 days as well as mortality declining from 12% to 8%.Conclusion: Automated integration of real-time laboratory data stream substantially improves dosing accuracy, decreases negative events and achieves better clinical results in monitored patients in real time. These results demonstrate the need for now short wave systems to be deployed in tertiary hospitals in order to improve the quality of patient services and working efficiency.